Factors Affecting Students' Decisions in Choosing to Study for a Master's Degree of Souphanouvong University: https://doi.org/10.69692/SUJMRD100465 - CHANTHAMANYVONG, Keo; Duangvilaykeo, Thipphavan; Saibounbhang, Saithala (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study was to investigate: 1) the level of students' opinions on the importance of factors that encourage students to study for the Master's program of Souphanouvong University, and 2) factors affecting students' decisions in choosing to study for the Master's program of Souphanouvong University. This study was conducted a quantitative and qualitative study, the sample group are 220 students who have graduated and are studying at the master's level of Souphanouvong University, using the questionnaires as a tool in the study, the statistics analysis were mean, Standard Deviation, and Regression multiple analysis. The result of the study found that 1) the level of students' opinions on the importance of factors that encourage students to study for the Master's degree of Souphanouvong University as a whole gives a high level of importance with 4.15 and S.D=0.46, which includes the course advertising factor at many levels with 4.15 and S.D=0.46, motivational factors with 4.14 and S.D=46, and maintenance factor with 4.07 and S.D= 0.54. 2) Factors affecting students' decisions in choosing to study for the Master's degree of Souphanouvong University include personnel development factors, teachers (professors), environmental factors and learning resources, scientific research factors and academic services with a statistical significance level of 0.05.